111 Sex differences in the association between video gaming and violence among urban youth. (19th September 2017) - Goldstick, Jason; Roche, Jessica; Carter, Patrick; Arterberry, Brooke; Bonar, Erin; Walton, Maureen; Zimmerman, Marc
Abstract : Statement of purpose: Empirical studies of the relationship between aggression and playing violent video games have produced mixed results; one possible reason is the inattention to effect modifiers, such as sex. Our purpose is to analyse the relationship between serious violence perpetration and video gaming frequency among a sample of urban youth, and how that relationship varies by sex. Methods/Approach: We analysed baseline data from a quasi-experimental intervention study of youth violence. Youth aged 14–20 were recruited at a Level 1 urban emergency department from October 2011 to March 2015. Participants self-administered a computerised survey including measures of demographics, substance use (alcohol/marijuana), violence perpetration, and number of hours per week of video gaming. The primary outcome was an indicator of any serious violence perpetration (e.g., weapon violence). Using logistic regression, we estimated the effect of gaming on serious violence perpetration, and how it varied by sex, while controlling for demographics, substance use, community violence exposure, and violence attitudes. Results: 409 individuals (60.0% female) enrolled in the study. Males (M=2.5, SD=2.8) played video games more hours per week than females (M=0.8, SD=1.8); the majority in both sexes reported violent games (action/fighting/shooting games) as their favourite genre. Gaming was associated with serious violence perpetration in females (OR=1.36, 95% CI =[1.13, 1.71]), but not males (OR=1.03, 95% CI =[0.89, 1.18]); in the model including both males and females, the interaction between gaming and sex was significant (p=0.02). Conclusion: Video gaming is more associated with excess risk of serious violence perpetration in females than males, possibly indicating that gaming is more normative among males, and more indicative of delinquency in females. Significance/Contribution: Violence prevention efforts, particularly among females, should consider the role of video gaming. Studies of what drives video gaming frequency in females may provide information relevant to violence prevention.